Back-end website development for IoT-based automated water dissolved oxygen control - Mahaasin, Habib Irfan; Kusuma, Purba Daru; Hasibuan, Faisal Candrasyah (Universitas Telkom, 2025)
The process of fish farming will never be separated from dissolved oxygen level control devices such as aerators so that the cultured fish can grow and develop optimally. This is quite troublesome for fish farmers, especially for people who often leave their cultivation sites, so they cannot monitor directly. Therefore, a platform for remote monitoring is needed. This journal focuses on designing and developing a back-end system, one of which functions as a data communication medium from the IOT antares platform to the website built so that the website can be used to monitor and control IOT devices using the waterfall development method and HTTP communication protocol. this method and communication protocol were chosen because they are currently quite popular and very flexible to use. The results of this research show that data communication carried out by the server with Antares using the GO programming language can run well and quite efficiently. The system built is also able to accommodate several requests from users simultaneously with an average response time of 60ms, while the exchange of IOT device data with the website has an average response time of 3 seconds.